High calcium fly ash-auto glass powder alkali-activated pastes - Yuwadee Zaetang; Pemiga Thongrit; Tanakorn Phoo-Ngernkham; Chayanee Tippayasam; Phanwatt Phungsai; Ampol Wongsa; Vanchai Sata; Prinya Chindaprasirt (International Journal of Sustainable Engineering)
Effective management of auto glass waste is essential for environmental sustainability, with recycling as pivotal strategies. This study aimed to valorise auto glass waste as a raw material for high-performance geopolymer composites. In the experiment, 0–40% auto glass powder (AGP) by weight was used as a substitute for high-calcium fly ash in the geopolymer paste. The setting time, workability, compressive strength, heavy metals leaching potential, and morphology of the geopolymer composites were investigated. The increase in the AGP content significantly increased the flow value and the setting time. The use of 10% AGP resulted in the paste with the highest compressive strength, and the 20% AGP paste displayed an acceptable compressive strength of approximately 90% compared to the reference paste. Microstructure analysis confirmed that an optimised AGP content of 10% resulted in a dense and homogenous geopolymer matrix with high compressive strength. Moreover, AGP inclusion also decreased the leaching potential of heavy metals, including chromium, copper, cobalt, zinc, nickel, and aluminium from fly ash geopolymer paste, making it more environmentally friendly. This research could thus lay a foundation for the development of guidelines for integrating AGP into geopolymer production, thereby encouraging eco-friendly practices in the construction sector.